2013
DOI: 10.1093/ehjci/jet159
|View full text |Cite
|
Sign up to set email alerts
|

Use of speckle strain to assess left ventricular responses to cardiotoxic chemotherapy and cardioprotection

Abstract: GLS is an effective parameter for identifying systolic dysfunction (which appears worst with combined anthracycline and trastuzumab therapy) and responds to cardioprotection in patients administered beta-blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
130
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(151 citation statements)
references
References 31 publications
6
130
1
14
Order By: Relevance
“…Future studies with larger number of patients may be able to evaluate a more accurate time course of the cardiac dysfunction and to detect it earlier in patients with childhood cancer after anthracycline treatment. These findings have important clinical implications and may allow for early therapeutic intervention, such as β-blockers, 12 for subclinical LV dysfunction to prevent LV dysfunction, and angiotensinconverting enzyme inhibitors 35 and angiotensin-receptor blockers to reduce wall stress and potentially improve the impairment of myocardial deformation. Furthermore, this parameter could allow better evaluation of the therapeutic effects of these medications.…”
Section: Discussionmentioning
confidence: 95%
“…Future studies with larger number of patients may be able to evaluate a more accurate time course of the cardiac dysfunction and to detect it earlier in patients with childhood cancer after anthracycline treatment. These findings have important clinical implications and may allow for early therapeutic intervention, such as β-blockers, 12 for subclinical LV dysfunction to prevent LV dysfunction, and angiotensinconverting enzyme inhibitors 35 and angiotensin-receptor blockers to reduce wall stress and potentially improve the impairment of myocardial deformation. Furthermore, this parameter could allow better evaluation of the therapeutic effects of these medications.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work has demonstrated that in patients receiving cardiotoxic chemotherapy, β-blocker administration reversed worsening of longitudinal strain. 46 Recently, extracorporeal removal of sFlt1 has been shown to improve pregnancy outcomes in women with preeclampsia. 47,48 Whether such therapies have a protective effect on the heart remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Obecnie nie ma dowodów, aby podejmować decyzje o zastosowaniu leczenia kardioprotekcyjnego, jeżeli stwierdzi się wczesne cechy subklinicznej dysfunkcji mięśnia sercowego, dokonując pomiarów GLS podczas kontrolnych badań echokardiograficznych [85,90,250]. Ocena GLS może być bardziej czułym narzędziem wykrywania wczesnej kardiotoksyczności, ale na podstawie obecnie dostępnych danych nie należy odstawiać, czasowo przerywać lub zmniejszać dawki leczenia onkologicznego na podstawie samego nowo wykrytego zmniejszenia GLS.…”
Section: Pacjenci Z Bezobjawowym Zmniejszeniem Globalnego Skurczowegounclassified